Sustainability of EU Food Safety Certification: A survival analysis of firm decisions - Ragasa, Catherine; Thornsbury, Suzanne; Joshi, Satish (International Food Policy Research Institute, 2013)
This study aims to understand the implications of stricter food safety regulations and certification systems to the food industry and to find ways to manage risks and costs associated with these regulations and systems. This paper empirically examines the timing of initial decisions to adopt food safety systems and subsequent decisions to maintain the certification. Survival models are used to evaluate firm-level decisions among seafood processors in the Philippines. Whereas initial certification decisions were influenced mainly by easily obtainable a priori indicators such as output price, scale of production, and association membership, decisions to continue certification were influenced by a larger number of less-visible factors including price differentials across markets and cost structures. Managerial hubris may have played a role in initial certification decisions, but decertification decisions were more informed by realized cost–benefit comparisons.